Very Low Frequencies Maintain Pain Relief From Dorsal Root Ganglion Stimulation: An Evaluation of Dorsal Root Ganglion Neurostimulation Frequency Tapering. Issue 4 (23rd November 2020) - Chapman, Kenneth B.; Yousef, Tariq A.; Vissers, Kris C.; van Helmond, Noud; D. Stanton‐Hicks, Michael
Abstract: Background: Dorsal root ganglion neurostimulation (DRG‐S) is effective in treating various refractory chronic pain syndromes. In preclinical studies, DRG‐S at very low frequencies (<5 Hz) reduces excitatory output in the superficial dorsal horn. Clinically, we have also observed the effectiveness of DRG‐S at low frequencies. We conducted a case series to describe the effect of very low‐frequency DRG‐S stimulation on clinical outcomes. Materials and Methods: DRG‐S for refractory low back pain was initiated at parameters consistent with published values. Thereafter, the stimulation frequency of DRG‐S was reduced in a stepwise fashion to the lowest frequency that maintained pain relief. Pain intensity, disability, and general health status data were collected at baseline, prior to initiation of tapering, and at four weeks after each patient's lowest effective stimulation frequency was reached. Results: After device activation ( N = 20), DRG‐S frequency was tapered from 16 to 4 Hz over a 4‐ to 17‐week period, reducing charge‐per‐second by nearly two‐thirds. Even so, pain relief was maintained at more than 75%, with consistent findings in the other measures. Conclusion: DRG‐S may have utility in treating chronic pain at lower stimulation frequencies than previously recognized. We have previously theorized that the mechanism of action may involve preferential recruitment of low‐threshold mechanoreceptor fibers via the endogenous opioid system. Of clinical relevance, lower frequency stimulation maintains DRG‐S efficacy regarding improvements in pain, disability, and quality of life. It can extend battery life and may potentially lead to the development of smaller implantable pulse generators.